Pattern recognition - Gibson, William, 1948- (New York : Berkley Books, 2005)
American design consultant Cayce Pollard is hired by a London advertiser to find the creator of an Internet montage of video snippets that is gaining cult popularity--Cayce herself one of its hooked viewers--and her search turns up unexpected clues about her father's disappearance during the events of September 11.
Library Journal
School Library Journal
Wilson's Fiction
Booklist, November 2002
Kirkus Starred, November 2002
Library Journal, February 2003
Keywords: Business intelligence -- Fiction; Women private investigators -- England -- London -- Fiction; Business ethics -- Fiction; Mystery fiction; Women private investigators -- Fiction; London (England) -- Fiction; London (England) -- Fiction; Mystery fiction